2010
DOI: 10.1542/peds.2009-3506
|View full text |Cite
|
Sign up to set email alerts
|

Patent Ductus Arteriosus of the Preterm Infant

Abstract: A persistently patent ductus arteriosus (PDA) in preterm infants can have significant clinical consequences, particularly during the recovery period from respiratory distress syndrome. With improvement of ventilation and oxygenation, the pulmonary vascular resistance decreases early and rapidly, especially in very immature infants with extremely low birth weight (<1000 g). Subsequently, the left-to-right shunt through the ductus arteriosus (DA) is augmented, thereby increasing pulmonary blood flow, which leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
399
1
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 467 publications
(424 citation statements)
references
References 105 publications
7
399
1
17
Order By: Relevance
“…As in other studies the current data showed a significant association between PDA and BPD (p=0.002) (Table 4) [6,9,15,20,21,25,41,42,47,[66][67][68][69]. An almost similar risk was reported by Marshall et al in VLBW infants (BW <1500 g) [69].…”
Section: Respiratory Distress Syndrome and Patent Ductus Arteriosus Isupporting
confidence: 88%
See 4 more Smart Citations
“…As in other studies the current data showed a significant association between PDA and BPD (p=0.002) (Table 4) [6,9,15,20,21,25,41,42,47,[66][67][68][69]. An almost similar risk was reported by Marshall et al in VLBW infants (BW <1500 g) [69].…”
Section: Respiratory Distress Syndrome and Patent Ductus Arteriosus Isupporting
confidence: 88%
“…A link between PDA and IVH has been reported in many studies, as in the current report where there was an increased risk for IVH in Group 1 compared to Group 2 [20,40,46,47,68] (Table 4).…”
Section: Patent Ductus Arteriosus Intraventricular Hemorrhage and Pesupporting
confidence: 72%
See 3 more Smart Citations